What is wrong in extinguishing a species? Charting the Ethical Challenges of using Gene-Drive Technologies to eradicate A. gambiae vector populations (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
This article analyses three ethical arguments against the use of gene-drive technologies to control for, and possibly extinguish, a particular species of vector mosquitoes (Anopheles gambiae) causing the malaria infection. We conclude that none of these arguments is truly persuasive in the specific case and, therefore, that using gene-drive technologies to suppress or eradicate the population of Anopheles gambiae could be ethically justifiable provided certain cautions referring to ecological consequences, evolutionary effects and social engagement of local communities.
Keywords: Gene-Drive; genome-editing; bioethics; CRISPR-Cas9; biodiversity